Determinants of women’s empowerment through rural finance in Kongo central, Democratic Republic of Congo - Mandiangu, Israel; Mapapa, Augustin Mbangala; Cornet, Annie; Burny, Philippe; Lebailly, Philippe (Asian Development Policy Review, 2024)
This study examines women’s empowerment in Kongo Central Province, Democratic Republic of the Congo focusing on rural financing. A survey of 500 households analyzed through regression shows a significant impact of rural especially informal, finance on women’s autonomy. Access to finance boosts women’s economic activity, family income contribution, decision-making power and independence. The study reveals socio-economic disparities influenced by education, marital status, age and income. Education, marital status and income are important to empowering women in Central Kongo. Structural reforms are needed to remove systemic barriers to equitable financial inclusion. Key findings suggest that targeted policy interventions could improve rural women’s living conditions. Policymakers and stakeholders in rural development should adopt a systemic approach to promote gender equality and sustainable development. This research highlights the importance of tailored policies that meet rural women’s unique needs advocating for inclusive financial systems that empower women in economic and decision-making roles. This study offers crucial insights for enhancing women’s empowerment in rural areas emphasizing the need for focused interventions to achieve gender equality and sustainable progress in Kongo Central. These findings highlight rural finance as a powerful tool for boosting women’s autonomy and fostering broader socio-economic development in the region.